Implementation of a Web-Based Attendance System for Internship Monitoring in a Public Institution - Arbi Ardian, Dimas; Muhamad Ikhsan Thohir (Edumedia Solution, 2026)
The increasing number of internship participants in public institutions requires an efficient attendance monitoring system. The Sukabumi City Statistics Office previously relied on manual attendance records, which limited monitoring accuracy and efficiency. This community engagement activity aimed to develop and implement a web-based attendance system to support digital monitoring of internship participants. The system was developed using the Laravel framework and Tailwind CSS through stages of needs analysis, system design, development, testing, and deployment. Key features include user authentication, daily attendance submission, activity reporting, location verification, and attendance recapitulation. The results indicate improved efficiency, accuracy, and transparency in attendance management. Administrators can monitor attendance in real time, while participants benefit from a more structured digital process. This activity supports digital transformation in public-sector internship management.